Factors influencing consumers' perception in the choice of consumers’ products: a SEM approach on Malaysian consumers’ - Haque, A. K. M. Ahasanul; Rahman, Sabbir; Abd. Manaf, Noor Hazilah (JM Academy, 2010)
The overall purpose of this study is to identify the perception of Malaysian customers' in the choice of products and marketing price. A total of 300 usable surveys were obtained from university students from Kuala Lumpur, Malaysia. In additio, exploratory factor analysis, confirmatory factor analysis and structural equation modeling were applied to proof the hypotheses. The research results highlighted that the Malaysian consumers are very much influenced by ethnocentrism and their demographic backgroumd before they purchase any products. The results of this Research also suggest that a significant proportion of consumers' are not interested in country-of-origin, brand image, product quality information before making a purchase decision.